Preparations offered to workers in different food services: application of the score for qualitative assessment of preparations - Dohms, Pietra Oselame da Silva; Stangarlin-Fiori, Lize; Medeiros, Caroline Opolski (Frontiers in Nutrition, 2024)
The quality of preparations offered in the workplace can vary according to the different segments of food services and may impact workers' health. This study aimed to qualitatively assess food preparations offered to workers in different food services. A total of 384 preparations offered to workers in three segments of food services were evaluated: commercial (pilot study), non-commercial, and outsourced, selected for convenience, in the city of Curitiba, Brazil. To identify the preparations, an interview was carried out with the nutritionist in addition to the monitoring of the production process. The Score for Qualitative Assessment of Preparations (EAQP) was applied to evaluate the preparations, and the preparations were classified according to their quality: high, intermediate, low, and very low quality. Chi-square and Kruskal-Wallis tests with post hoc DMS were used. Most of the preparations were of high quality (72.9%), using mainly unprocessed or minimally processed ingredients. The preparations offered in the non-commercial food service had a better mean quality score when compared to other food services (p<0.01). This knowledge is essential to help food service professionals decide and choose the ingredients used in preparations.